PERBANDINGAN UJI FITOKIMIA PIPERINE PADA BUAH DAN DAUN CABE JAWA (Piper retrofractum VAHL.) DI KABUPATEN BANGKALAN, MADURA - -, Jamilatus Sa'diyah; Besse Khalidatunnisa; Dewi Sartika A; Musawira (BIOMA : JURNAL BIOLOGI MAKASSAR, 2026)
This study aims to compare the piperine content in the fruit and leaves of Javanese pepper (Piper retrofractum Vahl.) in six production centers in Bangkalan Regency, Madura, as a basis for mapping phytochemical potential and developing local phytopharmaceutical raw materials. The background of this study is based on the high demand for Javanese pepper as a spice and traditional medicine commodity, but productivity and optimal utilization of plant parts are still limited. Plant samples aged at least five years were taken from six subdistricts in Bangkalan Regency, then simplified powder was made, and piperine content was analyzed using the High Performance Liquid Chromatography (HPLC) method. The results showed significant variations in piperine content between subdistricts and plant organs. The highest piperine content in Javanese chili peppers was found in Burneh Subdistrict at 225.22 mg/g, while the lowest content in fruits was found in Tanjungbumi Subdistrict at 103.28 mg/g. In the leaves, the highest piperine content was found in Blega District at 19.18 mg/g, and the lowest content in the leaves was found in Burneh District at 5.73 mg/g. In the leaves, the highest piperine content was found in Blega District at 19.18 mg/g, and the lowest content in leaves was found in Burneh District at 5.73 mg/g. In general, the piperine content of the fruit was much higher than that of the leaves throughout the production area. These findings emphasize the importance of selecting plant parts and production locations to optimize the utilization of Javanese pepper as a source of active phytopharmaceutical ingredients, and serve as a basis for developing quality standards and downstream strategies for herbal products in Bangkalan District, Madura.